Genus-level macroinvertebrate methods limit the conservation coverage afforded aquatic species - Robinson, Jason L. (Frontiers in Ecology and Evolution, 2023)
Benthic macroinvertebrate protocols, in the United States, have been integral in the implementation of the Clean Water Act (33 U.S.C. §1251 et seq. (1972)). The methods in these protocols are designed to describe patterns of biological water quality and ecological condition relevant to legislative oversight, and require a tradeoff between taxonomic precision and protocol simplicity. The global similarity of ecological and evolutionary responses to the challenges of life in flowing waters, by stream organisms, has greatly facilitated the development and implementation of biological data from freshwater mussels, fishes and aquatic insects into streamlined regulatory frameworks. Unfortunately, the factors that expedite the use of benthic data into ecological descriptions sufficient for regulatory processes (taxonomic generalizations, standardization of sampling procedures to focus on a narrow subset of available habitats) also limit the utility of these methods in the conservation of benthic macroinvertebrate species (the large majority of which are insects). Using simple hypothetical simulations, some examples from a taxonomic and ecological database of one state in the U.S.A. (Illinois), and data from a large-scale inventory of aquatic insect species in a network of U.S. National Parks, I illustrate how these methods are limited in their ability to effectively describe ecological patterns relevant to the conservation of aquatic insect species. I identify, challenge, and explore three basic assumptions implicit to the genus- and family-level identification methods widely used in freshwater benthic science, then discuss how the failure of these assumptions can create empirical, theoretical and philosophical obstacles to the interpretation of data. I offer some hopeful suggestions for improving aquatic insect species conservation that are within the reach of all benthic freshwater ecologists.